The small voice of history: collected essays - Guha, Ranjit; Chatterjee, Parth (Permanent Black Ranikhet, 2010)
These writings have been put together by Partha Chatterjee, whose long association with Guha as a founder-member of the Subaltern Studies editorial board is complemented by his own international stature as a historian, political theorist, and public intellectual. Chatterjee?s Introduction sketches the professional life and intellectual trajectory of India?s most profoundly influential modern historian.Every serious student of South Asian history, politics, and anthropology will be enriched by the astonishing diversity of insights and learning within this book.
Keywords: India - History - British occupation, 1765-1947; India - Historiography